Frequência do aleitamento de lactentes Jersey - Santos, Maiane Cristina Rodrigues dos (2019)
Brazil is among the largest dairy producers in the world and the state of Paraná has increased milk production in 75% since 2006 reaching the third position in the national ranking in 2016. In order to keep increasing milk production the replacement of animals is a strategy that needs to be applied. In addition to genetics, the management of calves and heifers has influence on future performance. Among the strategies, lactation is important, and it has been proven that the supply of higher amounts of milk results in higher production in the first lactations and greater productive longevity. The aim of this study is to perform an experiment to compare the performance of animals fed with six liters of milk distributed in three daily feedings in comparison to the conventional two-feed system during the first 30 days of Jersey calves and heifers. The experiment was performed at the Dairy Cattle Teaching and Research Unit of the Federal Technological University of Paraná – Campus Dois Vizinhos. For the experiment, it was used eight newborn Jersey animals divided equally into two treatments. For each treatment, the animals were fed with six liters of raw milk in 2 or 3 meals per day from 0-30 days. For all the characteristics evaluated, there was no significant difference between the treatments, that is, the animals that received three meals a day had the same performance as the animals that received only two meals a day. Therefore, there is no need to increase the labor force on the part of the rural producers to provide the third daily meal, in the case of Jersey animals, with suckling of six liters/day.